2022
DOI: 10.31599/jki.v22i2.730
|View full text |Cite
|
Sign up to set email alerts
|

Literasi Keuangan Dan Perilaku Keuangan Berpengaruh Terhadap Perilaku Konsumtif Pada Player Call Of Duty: Mobile

Abstract: This study aims to determine and measure the influence of financial literacy and behavior on consumptive behavior in Call of Duty: Mobile players. The rapid development of the virtual world has become a scourge for its users in seeking entertainment through online games, this has become an opium effect for users of all ages and occupations, making them consumptive actors. This research is a quantitative research, where the object is used as a Call of Duty: Mobile player. The data processing method is carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
1
Order By: Relevance
“…Financial literacy encompasses activities aimed at acquiring knowledge through testing the skills required to shape attitudes, particularly in the context of financial management decisions (Financial Services Authority, 2022). According to Syafira, et al (2022), financial literacy is the science of understanding an individual's finances that will be implemented to make wise decisions. If someone has mastered the theory of financial literacy, they will make wise consumption choices (Mubarokah & Pratiwi, 2022).…”
Section: Financial Literacymentioning
confidence: 99%
“…Financial literacy encompasses activities aimed at acquiring knowledge through testing the skills required to shape attitudes, particularly in the context of financial management decisions (Financial Services Authority, 2022). According to Syafira, et al (2022), financial literacy is the science of understanding an individual's finances that will be implemented to make wise decisions. If someone has mastered the theory of financial literacy, they will make wise consumption choices (Mubarokah & Pratiwi, 2022).…”
Section: Financial Literacymentioning
confidence: 99%
“…Mobile Legends adalah permainan video online bergenre MOBA yang dikembangkan oleh Moonton, sebuah perusahaan pengembang permainan asal Tiongkok. Mobile Legends diluncurkan pada tahun 2016 dan sejak itu telah menjadi salah satu permainan video online terlaris di dunia [6]. Menurut data dari Sensor Tower, sebuah platform analisis data aplikasi seluler, Mobile Legends telah diunduh lebih dari 500 juta kali di Google Play Store dan App Store hingga September 2020.…”
Section: Pendahuluanunclassified
“…However, contrasting results were presented by Risnawati et al [33] and Pohan et al [34], indicating no significant impact between lifestyle and consumptive behavior. These studies collectively highlight the complexity of understanding the interplay between lifestyle choices and consumptive behavior.Financial literacy refers to individuals' understanding and knowledge of financial concepts, which serve as the foundation for decision-making in managing their financial aspects [35]. The increase in financial literacy in Indonesia nationally has experienced growth of 11.65%, rising from 38.03% in 2019 to 49.68% in 2022.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kotler & Keller [29], lifestyle is one of the factors influencing consumptive behavior. The influence of financial literacy on consumptive behavior can also be explained using the theory of planned behavior, as done by Fauzi & Sulistyowati [35]. Yahya [27] ISSN: 2722 -4015 http://ijstm.inarah.co.id 543 found that financial management depends on how well individuals understand, use their skills, and their beliefs, which will affect their financial attitudes and behaviors to avoid falling into consumptive behavior.…”
Section: Introductionmentioning
confidence: 99%